THE WORK OF A PSYCHOLOGIST TO DETERMINE A PROFILE SENIOR SCHOOL STUDY - Kapkanets Т.С. (Pedagogy of Higher and Secondary Education, 2022)
In article author considers the formation an profile of the education in senior school psychological accompaniment it. The Author gives the model professional orientation functioning the school psychologist with pupil 9-h classes on determination of the profile of the education in senior school.